The dissemination of knowledge in manufacturing enterprises using intranet based knowledge management system: an example / Norlida Buniyamin and Zainuddin Mohamad - Buniyamin, Norlida; Mohamad, Zainuddin (UiTM Press, 2008)
This paper reports the findings of research undertaken to investigate and improve the utilisation of knowledge in manufacturing enterprises based on literature reviews and case study carried out in a manufacturing enterprise in the United Kingdom. The research provided the evidence for 1) the need to manage, classify, categorise and map process knowledge and 2) the need for a Knowledge Management System (KMS) designed specifically for manufacturing enterprises based on knowledge mapping of the company's intranet to enable the timely exploitation, generation and re-utilisation of process data, information and knowledge. In addition, a prototype Knowledge Management System (KMS) designed specifically for manufacturing enterprises based on knowledge mapping is described. Further, an overview of knowledge management, knowledge mapping and a discussion of how manufacturing enterprises could be supported in the implementation of Continuous Improvement (CI) projects by efficient re-utilisation of knowledge via knowledge maps embedded with best practices and standard procedures is presented.